Organic Production of Banana Fibres for Pollution-free and Environmental Benefits - Shirisha , Tekkam; Payal, Mahadule; Trupti , Bhadke (Current Perspectives in Agriculture and Food Science Vol. 1, 2022)
The banana plant, (Musa paradisiaca) produces fibre for textiles in addition to its delicious fruit. It was known as "banana fibre." It thrives in hot, tropical climates and produces fresh shoots easily as it matures. Banana plants of every variety contain an abundance of fibres. These fibres, which belong to the category of bast fibres, are recovered after the fruit is picked. The pseudostem, or trunk, of the banana plant, is largely discarded as agricultural waste after fruit production. Since the outer sheath of pseudostems may be used to make around 1.5 million tonnes of dry banana fibres per year, these pseudostems can be successfully used in the manufacture of banana fibres. Waste from biomass (pseudostem), a rich source of natural fibres, can be profitably used for a variety of applications and the creation of a range of goods. Similar to glass fibre in strength, banana fibre has excellent explicit strength characteristics. Glass filaments are thinner in this material at that moment. Fine pillow covers, neckties, bags, tablecloths, curtains, etc. are also made from banana fibre. Banana silk fibre rugs are likewise highly well-liked all around the world. The biodegradability of these natural fibres, which are ultimately broken down into water and carbon dioxide by microorganisms in the soil, is their finest quality. In addition to having key qualities like low density, lightweight, strong tensile strength, fire and water resistance, banana fibres are also environmentally safe.